2008
DOI: 10.3748/wjg.14.4434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the potential of mesalazine to prevent colorectal cancer

Abstract: Patients with ulcerative colitis (UC) and Crohn's disease (CD) are at increased risk for developing colorectal cancer (CRC), and this is believed to be a result of chronic inflammation. Although conclusive evidence is still missing, both epidemiological and experimental observations suggest that certain drugs used to treat inflammation, such as mesalazine, can reduce the incidence of colitis-associated CRC. Therefore, in recent years, several studies have been conducted to dissect the mechanisms by which mesal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Interestingly, a retrospective study of patients with ulcerative colitis showed that those who were not on long-term SSZ or 5-aminosalicylic acid (5-ASA) therapy (the active moiety of SSZ) were significantly more likely to develop colorectal cancer than their compliant counterparts [44]. Both epidemiological and experimental observations suggest that SSZ or 5-ASA (mesalazine) can reduce the incidence of colitis-associated CRC [44][45][46]. Our current study nevertheless demonstrates the biochemical mechanism of the combination effect of SSZ and CDDP in CRC.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a retrospective study of patients with ulcerative colitis showed that those who were not on long-term SSZ or 5-aminosalicylic acid (5-ASA) therapy (the active moiety of SSZ) were significantly more likely to develop colorectal cancer than their compliant counterparts [44]. Both epidemiological and experimental observations suggest that SSZ or 5-ASA (mesalazine) can reduce the incidence of colitis-associated CRC [44][45][46]. Our current study nevertheless demonstrates the biochemical mechanism of the combination effect of SSZ and CDDP in CRC.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, both in vitro and in vivo studies have shown that mesalamine inhibits multiple biological pathways that sustain colon cancer cell growth, thereby reducing the risk of developing inflammatory bowel disease-related colon cancer (20)(21)(22). However, the antineoplastic effects of mesalamine are seen only with doses that are not always reached in the gut following oral administration of the drug (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…5-ASA reduces oxidative stress, inhibits cell proliferation and promotes apoptosis (Gasche, 2004;Stolfi et al, 2008b). At the molecular level, 5-ASA inhibits COX-2 (Peskar et al, 1987;Stolfi et al, 2008a), decreases transcriptional activity of NF-kB by modulating phosphorylation of RelA/p65 and interferes with Wnt pathway through protein phosphatase 2A (Egan et al, 1999;Bos et al, 2006).…”
Section: Conclusion and Implications For Therapy And Prophylaxismentioning
confidence: 99%